On Spacelike Biharmonic Slant Helices According to Bishop Frame in the Lorentzian Group of Rigid Motions E(1, 1) - Korpinar, Talat; Turhan, Essin (Soc Paranaense Matematica, 2012)
In this paper, we study spacelike biharmonic slant helices according to Bishop frame in the Lorentzian group of rigid motions E(1, 1). We characterize the spacelike biharmonic slant helices in terms of their curvatures in the Lorentzian group of rigid motions E(1, 1). Finally, we obtain parametric equations of spacelike biharmonic slant helices according to Bishop frame in the Lorentzian group of rigid motions E(1, 1).
Keywords: Biharmonic curve; Bishop frame; Rigid motions